Resiliensi Berbasis Religi Bagi Mantan PSK dan Mucikari Pasca penutupan Lokalisasi Gandul Tuban - Ridlwan, Mujib (Koordinatorat Perguruan Tinggi Agama Islam Swasta Wilayah IV Surabaya, 2015)
This article attempts to explain resilience (ability to adapt and to remain tough in critical and difficult situation) of prostitute women (Pekerja Seks Komersial or PSK) and procurers after the prostitution site of Gandul in Pakah, Gesing Village in Tuban Regency has been closed. The study aims to reveal not only the resilience of the ex-prostitute women (PSK) and procurers in dealing with difficult situation but it also tries expose the role of religion to help these people in dealing with resilience. To know whether the religion is able to play role in such situation, the writer along with a number of prominent figures of Gandul Village as well as the ex-prostitute women and procurers have initiated a set of religious activities. The religious activities provide these people a valuable matters and information about Islamic teachings such as prayer (salat), fasting, and charity. In addition, the activities also deal with social aspects. These activities aim to help the participants perform Islamic teachings correctly and live better.